Teaching Resources: Integrating Visual Arts: Humanities and Social Sciences Classrooms - EAA Editorial Office (Education About Asia, 2021)
Just as they enrich our lives, the visual arts have wonderful potential to stimulate students’ imaginations, intercultural understanding, and knowledge of other academic subjects. The following selections from the EAA archives should prove helpful for teachers and students from a wide range of academic disciplines including anthropology, history, communications, religion, philosophy, and art history courses. Each teaching resource essay has rich visuals, most include teaching questions and resources, and all can be useful for face-to-face and digital learning.
Keywords: Art History; China; East Asia; Education; Japan; Northeast Asia; Visual Arts